Developing a new statistical method for Chinese text segmentation - Dai, Yubin (2008)
A new statistical formula for Chinese text segmentation called Contextual Information Formula (OF) was developed empirically for identifying 2 and 3-character words. It was developed by performing stepwise logistic regression using a sample of sentences that had been manually segmented. 300 sentences were used for model building and 100 sentences were set aside for model validation and evaluation. Relative frequencies, document frequencies, weighted document frequencies, within-document frequencies of characters, bigrams and trigrams were included in the study.